On the distribution and history of Saami verbal derivatives in -š- - Kuokkala, Juha; Koponen, Eino (Eesti ja soome-ugri keeleteaduse ajakiri. Journal of Estonian and Finno-Ugric Linguistics, 2023)
Peer reviewed